GAMBARAN PEAK EXPIRATORY FLOW PADA PEKERJA PEMBANGUNAN JALAN TOL - Vanesa A'isy Maharani (2023)
Peak expiratory flow is the maximum volume of air that can be expelled by the lungs when breathing forcefully and forcefully. Toll road construction workers are often exposed to various air pollutants such as dust, vehicle fumes, and chemicals that can affect their lung health. Therefore, the peak expiratory flow is one of the important parameters for assessing the lung function of highway construction workers. Research conducted on toll road construction workers showed that there was a significant reduction in peak expiratory flow in those exposed to air pollutants compared to non-toll road construction workers. This can be caused by damage to lung tissue due to exposure to chemicals or inhaled air pollutant particles. The purpose of this study is to describe the peak expiratory flow of workers at the toll road construction. This research is a descriptive quantitative study using the Spirometry parameter to measure a person's lung capacity. This tool works by measuring the amount of air inhaled and exhaled by a person. The population in this study were 60 workers on the toll road construction and the sample taken was 37 workers. The results of the research conducted showed that the average peak expiratory flow of workers at the toll road construction was relatively low with an average age range of 26-35 years with active smoking habits, normal body mass index, working duration of 8-12 hours per day and work experience. about 2-5 years of work.